2007
DOI: 10.1158/0008-5472.can-07-1063
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Peripheral Macrophages and Brain Microglia Increases Brain Tumor Titers of Oncolytic Viruses

Abstract: Clinical trials have proven oncolytic virotherapy to be safe but not effective. We have shown that oncolytic viruses (OV) injected into intracranial gliomas established in rodents are rapidly cleared, and this is associated with up-regulation of markers (CD68 and CD163) of cells of monocytic lineage (monocytes/microglia/macrophages). However, it is unclear whether these cells directly impede intratumoral persistence of OV through phagocytosis and whether they infiltrate the tumor from the blood or the brain pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
159
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(169 citation statements)
references
References 46 publications
(90 reference statements)
9
159
1
Order By: Relevance
“…48 In contrast, accumulation of CD68-positive cells within the tumor bed was only observed around viral plaques. Whether the inflammatory cells were present due to natural killer cell-induced interferon-g or were they recruited by other means to phagocytose virus-lysed cells is not clear.…”
Section: Infiltration By Cd68-positive Cells In Areas Of Active Viralmentioning
confidence: 91%
“…48 In contrast, accumulation of CD68-positive cells within the tumor bed was only observed around viral plaques. Whether the inflammatory cells were present due to natural killer cell-induced interferon-g or were they recruited by other means to phagocytose virus-lysed cells is not clear.…”
Section: Infiltration By Cd68-positive Cells In Areas Of Active Viralmentioning
confidence: 91%
“…These studies demonstrated that cyclophosphamide is able to inhibit neutralizing antibody induction, macrophages, regulatory T cells (Tregs) induction and intratumoral interferon (IFN)-g production. [2][3][4][5][6][7][8] It remains to be determined, however, how much this approach will benefit cancer patients who often have already various degrees of 'pre-existing' immunosuppression due to disease and chemotherapy.…”
Section: Suppression Of Innate Immune Response Enhances Efficacymentioning
confidence: 99%
“…10,18 In vivo, the absence of the E3B immuno-modulatory genes has also been suggested to prevent efficient spread of this mutant. 19,20 More recently, improved oncolytic viruses have been engineered with smaller specific gene deletions to retain viral potency. Several of these mutants target the pRb/p16 pathway by deletion of the small E1ACR2 domain, essential for pRb binding and inactivation, and S-phase entry to support viral replication and propagation.…”
Section: Introductionmentioning
confidence: 99%